META-ANALISIS HUBUNGAN SELF ESTEEM DENGAN ACADEMIC ACHIEVEMENT - Rahim, Fatmawati; Yudiarso, Ananta (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Literature about relation between Self-esteem and academic achievement was analyzed and reviewed. Method Reviewing fourteen literature (international journal) and using Meta-analysis method to correlation effect size self esteem for academic achievement. Result from fourteen literature indicate that self-esteem and academic achievement have medium effect size correlation (r= 0,448 with higher heteregonity (I2= 96,7%) and without publication bias (E= 0,09). Conclusion there is indirect correlation size effect correlation between self-esteem and academic achievement.